2011
DOI: 10.1080/02626667.2010.546358
|View full text |Cite
|
Sign up to set email alerts
|

Improving the performance of data-driven techniques through data pre-processing for modelling daily reservoir inflow

Abstract: The effect of data pre-processing while developing artificial intelligence (AI) -based data-driven techniques, such as artificial neural networks (ANN), model trees (MT) and linear genetic programming (LGP), is studied for Pawana Reservoir in Maharashtra, India. The daily one-step-ahead inflow forecasts are compared with flows generated from a univariate autoregressive integrated moving average (ARIMA) model. For the full-year data series, a large error is found mainly due to the occurrence of zero values, sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Then the output error is computed, and the error is backpropagated across the network. An analytical discussion of BPTT is available in Werbos [27], Jothiprakash and Kote [28].…”
Section: Tlrn Modelmentioning
confidence: 99%
“…Then the output error is computed, and the error is backpropagated across the network. An analytical discussion of BPTT is available in Werbos [27], Jothiprakash and Kote [28].…”
Section: Tlrn Modelmentioning
confidence: 99%
“…One of the well-known computational intelligence techniques used for modelling reservoir water release decision and forecasting is the Artificial Neural Network (ANN) (Nazri et al, 2013;Mokhtar et al, 2014;Wan Ishak et al, 2015). However, this technique suffers from poor interpretability, since it is difficult for humans to explain the practicality and logical meaning behind the learned weights of the model (Jothiprakash & Kote, 2011;Kajornrit et al, 2013). This problem can be solved by the Adaptive Neuro Fuzzy Inference System (ANFIS).…”
Section: Introductionmentioning
confidence: 99%
“…They found that annual runoff forecast was improved using the particle swarm optimizing method based on empirical model decomposition. Jothiprakash and Kote [23] used data pre-processing for modelling daily reservoir inflow using a data-driven technique, and they found that intermittent inflow during the monsoon period alone could be modelled well, using the full year data, but model prediction accuracy increases when only the seasonal data set for the monsoon period is used. This simply implies that the information content in a series plays a big role in the model training, hence the prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…One can eliminate irrelevant data to produce faster learning, due to smaller data sets and due to the reduction of confusion caused by irrelevant data [25]. Most of the conventional pre-processing techniques, such as transformation and/or normalization of data, do not perform well, because of the large variation in magnitude and scale, as well as the presence of many zero values in data series [23]. Data from the real world are never perfect; it can be an incomplete record with missing information, occurrence of zeros, improper types, erroneous records, etc.…”
Section: Introductionmentioning
confidence: 99%